Tanggug Jawab Suami Istri Terhadap Hutang Bersama Setelah Penceraian - Sukur, Fatma Resdiana; Latupono, Barzah; Lakburlawal, Mahrita Aprilya (Faculty of Law Universitas Pattimura, 2024)
The responsibility of married couples in settling joint debts after divorce is a very important thing to study. The reason is, there is no provision in Indonesia's positive law that regulates the settlement of joint debts after the dissolution of a marriage, which results in the parties not knowing how to settle joint debts, and also in certain cases will cause losses to one of the parties, both husband and wife who bear a larger amount of debt so that there is an injustice in the distribution of the debt. The method used in this study is normative juridical, to analyze legal problems contained in laws and regulations. The results of the study show that regarding the position of joint property between husband and wife during marriage in accordance with article 35 paragraph (1) property obtained during the marriage period becomes joint property, and under joint control where its use must be with mutual consent. After divorce, if referring to article 37 of the Marriage Law, the joint property is divided according to their respective laws, but in general, the joint property is divided equally between the ex-husband and wife according to the property obtained during the marriage period. Regarding the responsibility for joint debts, referring to article 35, joint debts used to meet the needs of the household and by mutual consent can be considered part of the joint property and the responsibility of the debt must be divided equally between the ex-husband and wife in order to create justice.